FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN MASYARAKAT TERHADAP FASILITAS PUBLIK (STUDI KASUS: TAMAN AKCAYA KOTA PONTIANAK) - B1011141081, Tri Kusumayanti (Jurnal Pembangunan dan Pemerataan, 2018)
ABSTRACTThis study aimed to find out and analyze the level of community satisfaction with the Akcaya Park facility in Pontianak City. The study uses multiple linear regression analysis with the SPSS ver. 16. The population used is the community or visitors who come to Akcaya Park in Pontianak City. The sample used was 39 respondents to visitors to the Akcaya Park in Pontianak City using the random sampling method. The results of the multiple linear regression analysis that have been done are obtained Î³ = 0.411 + 0.069 + 0.466 . The most influential independent variable on the dependent variable is the park facility variable (0.466), followed by the public service quality variable (0.411), and finally the park situation variable (0.069). The results of the t test prove that all independent variables (the quality of public services, the situation of the park, park facilities) have a positive effect on the dependent variable, namely community satisfaction. The coefficient of determination (adjusted ) obtained is 0.539. This means that 53.9% of community satisfaction is influenced by the variables of the quality of public services, the situation of the park, and the facilities of the park, the remaining 47.1% is influenced by other variables.Keyword: quality of public service, the situation of park, park facilities, and community satisfaction.